Elotuzumab plus lenalidomide/dexamethasone for relapsed or refractory multiple myeloma: ELOQUENT-2 follow-up and post-hoc analyses on progression-free survival and tumour growth - Dimopoulos, Meletios A; Lonial, Sagar; White, Darrell; Moreau, Philippe; Palumbo, Antonio; San-Miguel, Jesus; Shpilberg, Ofer; Anderson, Kenneth; Grosicki, Sebastian; Spicka, Ivan; Walter-Croneck, Adam; Magen, Hila; et al. (British journal of haematology, 2017)
The randomized phase III ELOQUENT-2 study (NCT01239797) evaluated the efficacy and safety of elotuzumab + lenalidomide/dexamethasone (ELd) versus lenalidomide/dexamethasone (Ld) in relapsed/refractory multiple myeloma. ELd reduced the risk of disease progression/death by 30% versus Ld (hazard ratio [HR] 0·70). Median time from diagnosis was 3·5 years. We present extended 3-year follow-up data. Endpoints included progression-free survival (PFS), overall response rate (ORR) and interim overall survival (OS). Exploratory post-hoc analyses included impact of time from diagnosis and prior lines of therapy on PFS, and serum M-protein dynamic modelling. ORR was 79% (ELd) and 66% (Ld) (P = 0·0002). ELd reduced the risk of disease progression/death by 27% versus Ld (HR 0·73; P = 0·0014). Interim OS demonstrated a trend in favour of ELd (P = 0·0257); 1-, 2- and 3-year rates with ELd versus Ld were: 91% versus 83%, 73% versus 69% and 60% versus 53%. In patients with ≥ median time from diagnosis and one prior therapy, ELd resulted in a 53% reduction in the risk of progression/death versus Ld (HR 0·47). Serum M-protein dynamic modelling showed slower tumour regrowth with ELd. Adverse events were comparable between arms. ELd provided a durable and clinically relevant improvement in efficacy, with minimal incremental toxicity.
Keywords: Recurrence; dexamethason; Male; overall survival; Antineoplastic Combined Chemotherapy Protocols; následné studie; Kaplan-Meier Estimate; multiple myeloma; thalidomid; Kaplanův-Meierův odhad; Aged; Dexamethasone; Multiple Myeloma; mužské pohlaví; senioři; monoclonal antibody; imunoglobuliny; elotuzumab; recidiva; progression-free survival; Follow-Up Studies; Thalidomide; humanizované monoklonální protilátky; Antibodies, Monoclonal, Humanized; lidé; ženské pohlaví; Humans; protokoly protinádorové kombinované chemoterapie; lenalidomid; mnohočetný myelom; Female; Immunoglobulins; lidé středního věku; Lenalidomide; Middle Aged